(untitled) (Minerva. Revista de Filología Clásica, 2019)
Reseña de Gabriela Cerra, Linguistic Questions in Cicero’s Poetic Translations, Bahía Blanca, Editorial de la Universidad Nacional del Sur, 2009, 262 pp. ISBN 978-987-1620-10-4